Impact of the Covid-19 on global supply chain – some sectoral policy and economic responses and business intervention / Ahmad Naqiyuddin Bakar ... [et al.] - Bakar, Ahmad Naqiyuddin; Abdul Kadir, Juliana Mohamed; Miskam, Zamri; Zainon, Saunah; Samsudin, Syamsyul (2021)
The new coronavirus 2019 (COVID-19) has infected millions of people worldwide since its first occurrence in December 2019, in Wuhan, China (Torales et al., 2020). More than onethird of the world population had been under some type of restriction. A total of 48 countries implemented partial or full lockdown and among these countries, Brazil, France, Italy, New Zealand, Poland, and the UK have implemented the world's longest and most restrictive lockdown (Langton, 2020). Despite widespread concern and action, the continuous rate of infection and death because of the COVID-19 pandemic has caused a severe economic downturn around the world (Kells, 2020). Under rapid globalization, firms face increasing levels of uncertainty and, thus, a greater risk of supply chain disruption. A further problem is that supply networks now span multiple geographic regions, exposing managers to greater environmental and operational risks (Sato et al., 2020). This has led to social distancing, lockdown of towns and cities to prevent transmission of the virus, and the need for anyone involved in the frontline to wear personal protective equipment. However, the need for lockdown and social distancing meant that all elements of the supply chain in many economic sectors were interrupted, including manufacturing, procurement, distribution, and supplies. These significant restrictions on transportation and movement have led to significant socioeconomic effects on people's livelihoods, even leading to an economic recession. The remainder of this article is organized as follows. Following this section, we report the data source and the design of this study. Next, in the discussion section, we summarise the policy, economic, and business responses to address the challenges followed by some reflections on them. Last not but not least, some conclusions and a direction for future study are offered.